Effect of stress on the ecophysiological response of the sand dollar Dendraster excentricus from northwestern Mexico - Olivares-Bañuelos, Tatiana; Figueroa-Flores, Salvador; Carpizo-Ituarte, Eugenio (Ciencias marinas, 2014)
In the Mexican Pacific, Dendraster excentricus, a common estuarine echinoderm, is subject to daily environmental variations in tidal fluxes. Little is known about its ecophysiological response when individuals are exposed to temperature and oxygen changes. This study evaluates their thermal stress response under normal and reduced oxygen conditions using the RNA/DNA ratio and hsp70 gene expression. We exposed sand dollars to different temperature and oxygen conditions. Three experimental temperatures were similar to the ones that organisms experience during one annual cycle and two were considered extreme. Reduced oxygen conditions were considered when levels dropped below 4 mg L–1. To estimate variations in the stress-induced RNA/DNA ratio, we determined the value for males and females during a daily cycle. We also analyzed the hsp70 expression. Under stress conditions, a significant decrease was observed in the RNA/DNA ratios. The lowest values were detected after 6 h under normoxic conditions and high temperatures seemed to induce a major effect on the RNA/DNA ratios during the first hour of stress. Analysis of the hsp70 expression showed significant differences. According to our results, thermal and reduced oxygen stress induces a reduction in the general metabolism of the organisms. These metabolic changes were observed by the decrease in the RNA/DNA ratios and expression levels of hsp70 (at high temperatures). We conclude that RNA/DNA ratios are a useful ecophysiological tool to evaluate the effect of particular stressors on the physiology of D. excentricus, and seem to be more sensitive to oxygen levels than to thermal stress, in contrast to the hsp70 expression, which was more sensitive to extreme temperatures.